Endovascular thrombectomy: 31 hours from symptom onset. Issue 1 (7th January 2020) - Beharry, James; Duncan, Roderick; Krauss, Martin; Colgan, Frances; Lim, Jen Yuh; Wu, Teddy
Abstract : Endovascular thrombectomy is an effective intervention for symptomatic intracranial large-vessel occlusion. This treatment has proven benefit up to 24 hours following onset in selected patients with prestroke functional independence. Limited case reports suggest that thrombectomy beyond 24 hours may also be effective. We describe a young woman managed with endovascular thrombectomy beyond 24 hours.